Technological factors associated with oil palm yield gaps in the Central Region in Colombia (2017)
This study builds on the results from a previous study (Ruiz, 2017), aimed to identify and quantify yield gaps in a sample of lots from small and medium scale producers, all suppliers of the same mill. The technical staff from the mill provides technical assistance to the aforementioned growers. This study was aimed at identifying what technological factors are associated with such gaps. Regarding the methodological approach, first, it was used the technology balance index (TBI) in order to quantify technology adoption. The TBI allows for rating technology adoption at oil palm crops by considering five processes (which comprehend 25 cropping practices). The processes evaluated are establishment, weeding and pruning, fertilizing, pests control and harvesting. The TBI assigns a category for each practice: high if it is fully adopted, intermediate if it is partially adopted and low if it is not adopted at all. Secondly, in order to determine those practices affecting yield gaps; we used a multiple correspondence analysis (MCA). MCA allowed to synthesize data into two dimensions with 51% of the variability given by the data gathered (qualification of the adoption of 25 crop management practices). Thirdly, we used cluster analysis in order to group lots according to adoption of technology. Then we related the obtained groups with the yield records. MCA results indicated that proper establishment, harvest and nutrition practices are the ones causing most of the variability in terms of technology adoption. The groups resulting from CA, provided evidence that a greater adoption of technology, leads greater yields (i.e. smaller yield gaps).